Сперматогенез у Biacetabulum appendiculatum (Szidat, 1937) Janiszewska, 1950 (Cestoda, Caryophyllidea) - Базитов, А.А.; Кулаковская, О.П.; Шестакова, К.А. (Вестник зоологии, 1979)
Morphology of Biacetabulum appendiculatum spermatogenesis is studied in slices stained by histological and histochemical methods. It is determined that cytophores are formed by spermatogonia before completion of reproductive divisions. The young cytophore contains above 10 nuclei of spermatogonia, the cytophore before maturation divisions contains 20 nuclei of primary spermatocytes, after maturation divisions — 80 nuclei of spermatids. Thus, a scheme of spermatogenesis in B. appendiculatum differs essentially from that in strobilated cestodes which contradicts the neoteny hypothesis.